Single-cell RNA sequencing analysis reveals the critical role of fibroblasts in aortic progeria-associated vascular remodeling in Hutchinson-Gilford progeria syndrome mice - Sun, Qian; Yang, Liehao; Zhou, Zilong; Wu, Nan; Li, Chunyi; Hu, Qianying; Cong, Xianling (Frontiers in Immunology, 2025)
BackgroundPatients with Hutchinson-Gilford progeria syndrome (HGPS) typically succumb to cardiovascular diseases in their teens. Although fibroblasts have been implicated in the progression of arteriosclerosis, their roles and mechanisms in progeroid aorta remain poorly understood.MethodsUtilizing single-cell RNA sequencing, we analyzed aortic tissues from HGPS mice with a focus on fibroblasts. Through gene expression profiling, Gene Ontology (GO) analysis, and cell-cell communication networks across various cell types, we revealed the unique contributions of fibroblasts during HGPS aortic aging. Finally, knockdown of Lgals3bp in HGPS cells was performed to investigate its role in inflammation and fibrosis.ResultsFibroblasts exhibited altered gene expression profiles associated with extracellular matrix dysregulation and inflammatory modulation, along with elevated senescence-associated secretory phenotype (SASP) scores in HGPS mice. Fibroblasts demonstrated the highest interaction frequency and intensity among aortic cell populations, with the strongest intercellular crosstalk observed between fibroblasts and dysfunctional vascular smooth muscle cells. We defined nine fibroblast subclusters and delineated their distinct transcriptional signatures, developmental trajectories, and interaction networks. Additionally, we identified significant upregulation of Lgals3bp in aortic fibroblasts of HGPS mice, which promoted the expression of pro-inflammatory factors and fibrosis-related genes.ConclusionOur findings underscore the pivotal role of fibroblasts in aortic progeria-associated vascular remodeling in HGPS mice and suggest that Lgals3bp may represent a potential therapeutic target for aortic pathology in HGPS.